T-cell Activation and E-selectin Are Associated With Coronary Plaque in HIV-infected Young Adults. Issue 1 (January 2017) - Mattingly, Aviva S.; Unsal, Aylin B.; Purdy, Julia B.; Gharib, Ahmed M.; Rupert, Adam; Kovacs, Joseph A.; McAreavey, Dorothea; Hazra, Rohan; Abd-Elmoniem, Khaled Z.; Hadigan, Colleen
Abstract : We evaluated immune activation and coronary artery plaque in young adults with human immunodeficiency virus acquired in early life (n = 31). Coronary plaque was positively associated with lipids, immune activation marker %CD8+CD38+DR+ and E-selectin, a marker of endothelial inflammation. Immune activation and endothelial inflammation may drive coronary plaque formation during the early stages of atherosclerosis in the context of chronic human immunodeficiency virus.